Safety and Effectiveness of Total Thyroidectomy and Its Comparison with Subtotal Thyroidectomy and Other Thyroid Surgeries: A Systematic Review. (24th February 2016) - Padur, Ashwini Aithal; Kumar, Naveen; Guru, Anitha; Badagabettu, Satheesha Nayak; Shanthakumar, Swamy Ravindra; Virupakshamurthy, Murlimanju Bukkambudhi; Patil, Jyothsna
Abstract : Diseases associated with the thyroid gland are one of the most frequently seen endocrine disorders across the globe. Total thyroidectomy is currently the preferred treatment for many thyroid diseases. Controversies exist among surgeons regarding safety of total thyroidectomy due to the risk associated with it like postoperative hypoparathyroidism or recurrent laryngeal nerve damage. Since, in the recent years, the incidence of thyroidectomy is in increasing trend in south Indian population, this review aims to study the available data regarding the appropriateness and safety of total thyroidectomy and compares it with subtotal thyroidectomy and other thyroid surgeries. This is a retrospective comprehensive review of various articles and publications regarding total and partial thyroidectomy performed across the world. Many retrospective studies and few prospective studies suggest that the incidence of transient hypocalcemia is higher after total thyroidectomy than after subtotal thyroidectomy, but the incidence of other complications including recurrent laryngeal nerve palsy and postoperative hematoma is not significantly different between the two procedures. Hence in our review we found that total thyroidectomy is safe and cost effective with low complication rates and provides little significant advantage of being safer procedure compared to subtotal thyroidectomy.